El principio de proporcionalidad y su recepción en el Código Procesal Penal de Nicaragua (Revista de Derecho, 2012)
DOI: http://dx.doi.org/10.5377/derecho.v0i1.743 Revista de Derecho No.1 2001 pp.263-274